Biochemical studies in drug-induced porphyrias in the rat : with a review of the literature on experimental porphyria and an investigation of thirteen human cases - Ginsburg, Aubrey David (Department of Integrative Biomedical Sciences (IBMS), 2020)
The group of disorders characterized by disturbances of porphyrin metabolism pose .many fascinating problems. The drug-induced porphyrias in animals provide a model whereby these problems may be investigated by techniques which cannot be applied to man. The consumption of alcoholic beverages or other chemical substances has been associated with the development of porphyrinuria and porphyria, but it is controversial whether these agents are of primary aetiological importance. or 'Whether they precipitate the· disease in genetically predisposed individuals. The Turkish epidemic of porphyrla has shown conclusively·that this disease may occur as an acquired condition in man. and a variety of compounds has been shown to be capable of inducing porphyria in animals.